Adam Smith and colonialism. (October 2014) - Williams, David
In the context of debates about liberalism and colonialism, the arguments of Adam Smith have been taken as illustrative of an important line of anti-colonial liberal thought. The reading of Smith presented here challenges this interpretation. It argues that Smith's opposition to colonial rule derived largely from its impact on the metropole, rather than on its impact on the conquered and colonised; that Smith recognised colonialism had brought 'improvement' in conquered territories and that Smith struggled to balance recognition of moral diversity with a universal moral framework and a commitment to a particular interpretation of progress through history. These arguments have a wider significance as they point towards some of the issues at stake in liberal anti-colonial arguments more generally.